Efektivitas pupuk organik cair ampas sagu dalam meningkatkan hasil tanaman kacang kedelai (glycine max l.) - Sartia Hama (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Soybean (Glycine max L.) is an important food commodity after rice in Indonesia, but domestic productivity is still low so that dependence on imports remains high. One strategy to increase sustainable productivity is through the use of liquid organic fertilizer (POC) based on organic waste, such as sago pulp (Metroxylon sagu), which contains essential nutrients and can improve soil fertility. This study aims to evaluate the effect of sago pulp POC application on the growth and yield of Wilis soybean variety. The study was conducted in Lamasi District, Luwu Regency, Palopo City in April–August 2024, using a non-factorial Randomized Block Design (RAK) with six POC concentration treatments (0, 50, 100, 150, 200, and 250 ml/L of water) and four replications. The parameters observed included plant height, flowering age, number of pods, and dry weight of pods. The results showed that the application of sago pulp POC had a significant effect on all parameters. The highest treatment (250 ml/L) produced maximum plant height (60.01 cm), the highest number of pods (168.42 pods), and the largest dry weight of pods (91.57 g). Meanwhile, the 100 ml/L treatment accelerated the flowering age to 37.42 HST. Sago pulp POC has been proven to be able to significantly increase vegetative and generative growth of soybeans, as well as being an alternative solution for environmentally friendly fertilization that supports sustainable agriculture and the independence of national soybean production.